Small fibre pathology in chronic whiplash‐associated disorder: A cross‐sectional study. (14th March 2020) - Farrell, Scott F.; Sterling, Michele; Irving‐Rodgers, Helen; Schmid, Annina B.
Abstract: Background: Mechanisms underpinning ongoing symptoms in chronic whiplash associated‐disorder (WAD) are not well understood. People with chronic WAD can exhibit sensory dysfunction consistent with small nerve fibre pathology, including thermal hypoaesthesia and hyperalgesia. This study investigated small fibre structure and function in chronic WAD. Methods: Twenty‐four people with chronic WAD (median [IQR] age 49 [15] years, 16 females) and 24 pain‐free controls (50 [17] years, 16 females) were recruited. Intraepidermal nerve fibre density (IENFD) and dermal innervation were assessed by skin biopsy. This was performed at (a) the lateral index finger on the primary side of pain and (b) superior to the lateral malleolus on the contralateral side. Quantitative sensory testing was performed over the hand. Results: The WAD group exhibited lower IENFD at the finger (WAD: median [IQR] 4.5 [4.9] fibres/mm; control 7.3 [3.9]; p  = .010), but not the ankle (WAD: mean [ SD ] 7.3 [3.7] fibres/mm; control 9.3 [3.8]; p  = .09). Dermal innervation was lower in the WAD group at the finger (WAD: median [IQR] 3.7 [2.8] nerve bundles/mm 2 ; controls: 4.9 [2.1]; p  = .017) but not the ankle (WAD: median [IQR] 2.1 [1.9] nerve bundles/mm 2 ; controls: 1.8 [1.8]; p  = .70). In the WAD group, hand thermal and light touch detection were impaired, and heat pain thresholds were lowered ( p  ≤ .037). Conclusions: Findings suggest small fibre structural and functional deficits in chronic WAD, implicating potential involvement of small fibre pathology. Significance: Our study found decreased intraepidermal nerve fibre density, reduced dermal innervation, thermal hypoaesthesia and hypersensitivity in people with chronic WAD, suggestive of small fibre pathology. This observation of peripheral nervous system pathology in chronic whiplash provides novel insights on mechanisms underpinning symptoms and challenges commonly held beliefs regarding this condition.